Description of Health Maintenance Behavior of Hypertension Sufferers in the Tayu Coastal Area - Andini Rahma Nidaul Izza; Beti Kristinawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Hypertension is a non-communicable disease problem in the world and in developing countries including Indonesia which can cause death by requiring serious treatment. Coastal communities are at risk of developing hypertension caused by foods that contain high salt and bad lifestyle. The purpose of this research is to find out the description of the health maintenance of hypertension sufferers in the coastal area of Tayu. This research is a quantitative descriptive study with a cross-sectional research design. This research was conducted in the coastal area of Tayu, Pati Regency in 5 villages namely Sambiroto, Keboromo, Ndororejo, Tunggul Sari, and Margomulyo villages. This research was conducted in February-March 2023. The population in this study were all hypertensive patients in the Tayu coastal area, totaling 644. The sample in this study was 247 people. Sampling technique with Accidental Sampling. Data collection in this study used the Self-Care of Hypertension (SC-HI) questionnaire. Analysis of this research data with descriptive Univariate analysis. The research results obtained were that the majority of hypertension sufferers in the Tayu coastal area were aged >65 years as many as 101 (40.9%). The majority of hypertension sufferers in the Tayu coastal area were female, 186 (75.3%). Most of the hypertension sufferers in the Tayu coastal area have elementary school education as many as 80 (32.4%). The majority of jobs in the Tayu coastal area work as housewives as many as 87 (35.2%). The majority of blood pressure in hypertension sufferers in the Tayu coastal area are at degree 2 (>140/90 mmHg). The description of maintenance behavior in hypertension sufferers in the Tayu coastal area, the majority of hypertension sufferers carry out health maintenance on a daily basis, namely 142 (57%) are still categorically bad. It is suggested to health workers to improve education about prevention of hypertension in the Coastal Areas in order to increase public knowledge, especially those with hypertension and it is suggested to health workers to carry out health checks for blood pressure in hypertension sufferers.Keyword: Coastal Area, Behavior, Health maintenance, Hypertension